PENGARUH MORAL WAJIB PAJAK ORANG PRIBADI TERHADAP PERSEPSI ATAS TAX EVASION DENGAN KEPATUHAN WAJIB PAJAK SEBAGAI VARIBEL MEDIASI - Indriyani, Joe Elsa; Sitawati, Riana; Subchan (Indonesian Journal of Accounting and Governance, 2018)
The purpose of this study is to be able to analyze the effect of moral on perception of tax evasionmediated by taxpayer compliance. Calculation of the number of research samples using Slovinformula, the sample in the study was as many as 100 questionnaires distributed directly in CentralSemarang Two Primary Tax Office with the permission of the official in charge of the Tax Office. Dataanalysis uses the WarpPLS 4.0 program with Partial Least Square (PLS) approach. The Results ofpreviois studies as follows moral has a positive effect on the compliance. Compliance has a negativeeffect on perception of tax evasion. Moral has a negative effect on perception of tax evasion.Compliance mediates the effect of moral on perception of tax evasion.